What is Pro-poor Growth? - Nanak Kakwani; Ernesto M. Pernia (Asian Development Review, 2000)
This paper attempts to explain the concept of “pro-poor growth”, and argues that it represents a major departure from the “trickle-down” phenomenon. It proposes a new indicator—the pro-poor growth index—that measures the degree to which growth can be considered to be pro-poor. The new indicator is used to analyze the nature of economic growth in three countries, namely, Republic of Korea, Lao People’s Democratic Republic, and Thailand.